PERAN KONSELOR ISLAMI DALAM PEMBINAAN AKHLAK DAN KEPRIBADIAN PESERTA DIDIK - Sukatin; Dimas Saputra; Wildan Mukholladun (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Islamic counselors play a strategic role in fostering the moral character and personality development of students through guidance and counseling services grounded in Islamic values. This article aims to analyze the role of Islamic counselors in shaping students’ personalities characterized by akhlaq al-karimah (noble character) within educational settings. This study employs a qualitative approach using a library research method, drawing upon the Qur’an, Hadith, and relevant scholarly literature related to Islamic counseling guidance and character education. The findings indicate that Islamic counselors play a crucial role in nurturing students’ moral and personal development through the application of advisory methods (mau‘izhah hasanah), exemplary conduct (uswah hasanah), and the habituation of positive behaviors. These approaches are effective in internalizing moral and spiritual values, thereby forming students who are faithful, pious, and responsible in their daily lives.